IMPLEMENTASI KEBIJAKAN INPASSING JABATAN GURU BUKAN PNS SMP SWASTA KABUPATEN KENDAL - Sutadi Sutadi (Departemen Administrasi Publik, Universitas Diponegoro, 2018)
One of the government's efforts in improving the quality of teachers is to implement the policy of determining the inpassing of functional positions of non-civil servant teachers and credit figures. According to Permendikbud number 47 of 2007 renewed Permendiknas no. 22 Year 2010 Inpassing Non Civil Servant Teachers (GBPNS) is the process of adjusting the rank of Non-Civil Servant Teachers to the rank of Master Civil Servant. Permendikbud Number 28 of 2014 renewed Permendikbud Number 12 of 2016 on the granting of equal positions and rank for non-civil servant teachers. Implementation of Inpassing Teacher Program Policy Non PNS SMP Kendal private sector concluded: a) All teachers who are certified educators are able to make a proposal document inpassing the positions of teachers instead of civil servants; b) All teachers remain a certified foundation of educators proposing SK inpassing; c) Only 10% of the proposals can be issued inpassing decree from the Ministry of Education and Culture. The results of research on the factors that inhibit the implementation of policy inpassing the position of junior high school teachers rather than civil servants in Kendal District: a) Communication Factor, the absence of communication between teacher or school with Ministry of Education and Culture related to proposal of inpassing of non-civil servant teacher position become one of the point that hinder the implementation of program; b) Factors Resources, lack of human resources administrative staff in private schools in this case associated with the fulfillment of standards of educational personnel to be one obstacle policy implementation; c) Disposition Factors, Understanding teachers, administrative staff, principals and officials of the District Education and Culture District of Kendal is a good factor driving the implementation of inpassing program. The conclusion of the policy implementation of inpassing of junior high school teachers rather than civil servants in private schools in Kendal District has not been successful.